Comparison of Rotavirus Genotypes Before and During the COVID-19 Pandemic - Ayşe ALICI; Elif Seren TANRIVERDİ; İlayda BUDAK; Murat AKKAN; Gülgün YENİŞEHİRLİ; Barış OTLU (Mediterranean Journal of Infection, Microbes and Antimicrobials)
Introduction: Rotaviruses are the leading cause of severe diarrhea in infants and young children worldwide. To date, 32 distinct G genotypes and 47 distinct P genotypes have been identified in group A rotaviruses. Following the Coronavirus disease-2019 (COVID-19) pandemic, our country implemented several measures that effectively reduced the incidence of infectious diseases, including acute gastroenteritis associated with COVID-19. In this study, we investigate whether the measures implemented following the COVID-19 pandemic led to changes in the rotavirus genotype distribution. Materials and Methods: A total of 128 stool samples that tested positive for rotavirus antigen - 64 from the pre-pandemic period and 64 from the pandemic period - were further analyzed for genotyping. As determined by reverse transcription-polymerase chain reaction, rotavirus RNA was detected in 50 (78%) samples from the pre-pandemic period and 51 (80%) samples from the pandemic period. Results: In the pre-pandemic period, the following results were observed among the patients studied by us: G9P[8] in 24 (48%), G1P[8] in 14 (28%), G2P[8] in five (10%), G2P[4] in three (6%), G3P[8] in two (4%), G4P[8] in one (2%), and G9P[4] in one (2%). During the pandemic period, the following results were observed in the patients studied by us: G9P[8] in 28 (54%), G1P[8] in 12 (24%), G2P[8] in six (12%), G2P[4] in two (4%), G3P[8] in one (2%), G4P[8] in one (2%), and G9P[4] in one (2%). Conclusion: In our study, G9P[8] was the dominant genotype during both periods, showing no significant difference in rotavirus genotypes between the pre-pandemic and pandemic periods.